The influence of cheerleading exercises on the demonstration of strength and endurance of 15-17-year-olds girls - N.V. Krivoruchko; I.P. Masliak; T.M. Bala; I.N. Skripka; V.I. Honcharenko (Physical Education of Students, 2018)
Purpose: to define dynamics of indicators of endurance and strength development of 15-17-year-olds girl-students after application of cheerleading exercises.